Synthesis of Cobalt Chromite Nanoparticles by Thermolysis of Mixed Cr3+ and Co2+ Chelates of 2-Mercaptopyridin N-Oxide - Edrissi, Mohammad.; Keshavarz, Ahmad Reza (Nano-Micro Letters, 2012)
Pure greenish-blue cobalt chromite (CoCr2O4) nanoparticles with narrow particle range of 4.1±1.9 nm and surface area of 78.2 m2g−1 were synthesized through mixed chelates thermolysis of corresponding metals using 2-Mercaptopyridine N-oxide sodium salt as chelating agent. During the thermolysis procedure, high amount of gases were emitted that led to the formation of nanoparticles with high surface area. The product was characterized by TGA, DTG, XRD, TEM, SEM, LLS, BET and chemical analysis. Design of experiments was performed to fulfill the two levels L4 Taguchi design. It was found that the temperature and time of thermolysis process have significant effect on the particle size reduction. The Oxidation of trichloroethylene was carried out over CoCr2O4 nanocrystallite. Catalytic activity analysis revealed that the synthesis CoCr2O4 possesses high catalytic activity for this process.